Strategic Directions for the Rural Territories Development of Agricultural Specialization (on the Example of the Altai Territory) - G. M. Gritsenko; М. V. Меshina; О. А. Povolotskaya (Управленческие науки)
The role of the municipal level in the country’s governance system is underestimated. Most of the rural areas are located far from the centers of socio-economic development with no ability for independent budget formation and the management of rural areas is carried out by untrained personnel. The Altai region has the largest number of rural municipalities and has agricultural specialization, so the subject of the article is the problems of rural areas’ development of agricultural specialization at the managerial level. The purpose of the study is to identify and substantiate the most important elements of rural areas to highlight it as an object of strategic planning. The directions and mechanisms of interaction should be taken into account in the complex programs of socio-economic development of rural areas, such approaches will attract investments to the territory, ensure the creation of new jobs and reduce the outflow of population to cities. The Altai territory is one of the pilot regions, where the use of digital technologies in agriculture is actively introduced, which emphasizes the importance of effective development of the region.